VAP Code: A Secure Graphical Password Scheme for Smart Devices - Azad, Saiful; Ranak, M. S. A. Noman; Rahman, Md. Arafatur (2016)
In recent times when consumers around the globe are embracing smart devices at a higher ratio, they are also turning into a point of attraction to the attackers. As a result, a considerable amount of attacks is noted on these devices in the recent past. To combat with these attacks, many password-based authentication schemes are proposed. Among them, graphical password schemes are more compatible for smart devices due to their heavily graphic-oriented nature. However, existing graphical password schemes experience various attacks and threats, e.g., shoulder surfing, smudge attack, intersection attack, reflection attack, brute force attack, and so on.